Performance Measures in Evaluating the Effectiveness of Teaching Methods and Skills in Karate - Mohammed Asim Ghazi (Department of Physical Education, Faculty of Health Sciences, Universitas Jenderal Soedirman, 2023)
Performance measures are crucial in evaluating the effectiveness of teaching methods and skills in karate. Studies have shown that using a program based on multiple intelligences can improve basic skills and cognitive load. Special training can also affect physical skill requirements in offensive karate kumite players. Factors such as general motor efficiency, specific speed, specific agility, and technical efficiency can also be identified. The study sample is chosen from karate athletes in preparatory schools and practitioners, with a sample size representative of the population of interest. Data collection tools include surveys, assessments, and observations. The study sample was chosen from Karate athletes in preparatory schools and 50 students of karate practitioners. A research design that includes quantitative and qualitative data collection techniques is used to evaluate the effectiveness of teaching methods and skills in karate. The study can be conducted in karate training centers or schools, and data analysis can be conducted using statistical methods to examine the relationship between performance measures and teaching methods. These results suggest that all teaching methods significantly impact the participants performance compared to the control group. Training methods used in the experiment group successfully enhanced karate performance. Ethical considerations must be taken into account when analyzing performance measures